Feed Efficiency and Growth Performance in Thai Beef Cattle Fed Cricket Meal as a Soybean Meal Replacement - Benjamad Khonkhaeng; Metha Wanapat; Sarong So; Areerat Lunpha; Ruangyote Pilajun; Pin Chanjula; Pichad Khejornsart; Pongsatorn Gunun; Nirawan Gunun; Bundit Tengjaroenkul; Sineenart Polyorach; Anusorn Cherdthong (My University, 2025)
Cricket ( Gryllus bimaculatus ) is a high‐protein insect species with a favorable amino acid and fatty acid profile, widely recognized as an alternative to soybean meal in nonruminant diets. However, research on its use in ruminant nutrition remains limited, particularly regarding its effects on feed efficiency and performance. This study evaluated the impact of completely replacing soybean meal with cricket meal on feed intake, nutrient digestibility, rumen fermentation, microbial populations, and growth performance in Thai native beef cattle. Eight male Thai native beef cattle (150 ± 15 kg; ∼2 years old) were used in a completely randomized design with two dietary treatments ( n = 4 per group). One group received a conventional soybean meal–based diet, while the other received a diet in which 100% of the soybean meal was replaced with cricket meal at an inclusion level of 12% of dry matter. Both diets were formulated to be isonitrogenous and isocaloric. Feed intake was similar between treatments. Crude protein digestibility was higher in the cricket meal group (67.5%) compared to the soybean meal group (63.7%; p = 0.04), while other digestibility parameters showed no differences. Blood metabolites, rumen fermentation characteristics, and microbial populations were unaffected by dietary treatment. Cattle fed the cricket meal‐based diet showed greater average daily gain (+55.7%; p = 0.02) and a 32.9% improvement in feed conversion ratio ( p = 0.02) compared to cattle fed the soybean meal–based diet. These results suggest that cricket meal can serve as a complete replacement for soybean meal in beef cattle diets, enhancing protein digestibility and growth performance without compromising rumen function.
Keywords: Insect Utilization and Effects